Mobile Colistin Resistance (MCR) Gene, Antimicrobial Resistance: A Global Public Health Threat (Bangladesh Journal of Medical Science, 2019)
Abstract not availableBangladesh Journal of Medical Science Vol.19(1) 2020 p.5-10